USING CUE CARDS IN TEACHING WRITING DESCRIPTIVE TEXT FOR JUNIOR HIGH SCHOOL 39 SURABAYA STUDENTS (RETAIN, 2016)
USING CUE CARDS IN TEACHING WRITING DESCRIPTIVE TEXT FOR JUNIOR HIGH SCHOOL 39 SURABAYA STUDENTS Gisella Kartika Arsadea English Education, Faculty of Languages and Arts, State University of Surabaya Gisella.arsadea@gmail.com Drs. Fahri.M,A Lecturer of English Study Program FBS Surabaya State University Fahri@unesa.ac.id Abstrak Di kelas dua sekolah menengah pertama, kompetensi dasar yang harus dikuasai murid dalam pelajaran menulis bahasa Inggris adalah kemampuan mengembangkan dan membuat teks fungsional sederhana dalam bentuk teks deskripsi, teks recount, dan teks narasi. Banyak murid yang menemui kesulitan dalam menulis tipe teks tertentu, khususnya teks deskripsi. Para guru dapat menggunakan cue card sebagai media dalam mengajar menulis deskripsi. Cue card adalah alat intruksi yang berguna bagi guru dan dapat diterapkan pada murid diberbagai usia. Cue card sangat mudah digunakan di dalam proses belajar mengajar. Sangat mudah bagi guru untuk membuat sendiri karena sangat sederhana dan murah. Cue card dapat menarik perhatian murid dan membuat mereka fokus di dalam topik. Dalam pengajaran teks deskripsi, cue card dapat di gunakan sebagai media yang membuat murid-murid mudah untuk mendeskripsikan sesuatu. Penelitian ini menggunakan penelitian deskriptive kualitativ. Instrument yang digunakan untuk mengumpulkan data adalah data observasi dalam bentuk catatan, tugas siswa, dan questionaire. Setelah di analisis, dapat di simpulkan bahwa cue card dapat digunakan sebagai media alternative untuk mengajar menulis teks deskripsi, khsususnya untuk kelas delapan sekolah mengeah pertama. Cue card efektif dalam membantu murid-murid untuk membuat teks deskripsi. Cue card dapat meminimalisir kesulitan yang murid hadapi dalam menulis. Cue card dapat memotivasi murid untuk menulis, membantu murid untuk membuat dan menggabungkan ide mereka dengan mudah. Selama proses belajar mengajar, kebanyakan murid memberikan respon positif terhadap penerapan cue card di kelas menulis. Hal ini terlihat dari antusiasme mereke, kebanyakan mereka merasa antusisas ketika guru memberikan cue card di setiap pertemuan. Kata Kunci: Cue cards, teks deskripsi Abstrak In the second grade of junior high school, the basic competency that should be achieved by students in the writing English subject is the ability to develop and produce written simple functional text in the descriptive text, recount text, and narrative text. Many students found difficulties in writing certain type of text, especially desciptive text. The teacher might use cue cards as the media of teaching descriptive writing. Cue cards are useful instructional tools for teachers to be used with students of any age. It can be easily used by teacher in teaching learning process. It is easy for teacher to make it and it is simple and cheap. Cue card can gather students attention or attract students to focus on the topic. In teaching descriptive text, cue card can be used as media that can make students easy to describe something. This study was designed in descriptive qualitative research. The instrument used to collect the data is observation in the form of field note, observation checklist, and questionaire. After being analyzed, it can be concluded that the cue cards could be used as an alternative media to teach writing descriptive text, espesially to the 8th grade students of Junior High School. The cue cards were effective in helping the students to compose their writing of descriptive text. The cue cards could minimize the students’ difficulties which they faced in writing. It motivates students to write, helped students to produce and organize ideas easily. During the teaching learning process, most of the students gave good responses toward the implementation of the cue card in writing class. This can be seen from their enthusiasm, most of them felt enthusiast whenever the teacher gave cue cards in every meeting. Key words: Cue cards, descriptive text